The melodic structure of the Armenian choir in Iraq (Al-Academy, 2026)
This research aims to study the choir in the Iraqi Armenian Church, which spans a century or more. Within the Armenian hymns, the musical artistic characteristics tend towards the globally recognized choir and systematic academic music and singing. Therefore, studying this art form is justified due to its significance and impact on building the Iraqi musical religious heritage and the secular systematic singing, especially since choral art lacks in-depth scientific studies within the Iraqi academic musical institutions that teach it.Specifically, the research focused on its primary objective of identifying the melodic structure of the Armenian choir and analyzing its basic voices in terms of harmony and melodic compositions according to the type of composition used in its preparation. This was based on musically notated models within the approved books of hymns of the Armenian Church in Iraq, which were reviewed in detail within the research literature. Additionally, the research reviewed its history, prominent composers, performance method, and its influence on and interaction with the musical artistic culture of the country.To this end, the researcher selected a model from the Armenian choir and subjected it to analysis according to a scientific standard specific to this field. This was done to reveal its melodic results based on the structural construction and the type of composition used, in order to draw conclusions that achieve the aim and objective of this study, as outlined in the body of the research.